2018
DOI: 10.21037/jss.2018.05.22
|View full text |Cite
|
Sign up to set email alerts
|

The impact of insurance coverage on access to orthopedic spine care

Abstract: Policy changes have expanded insurance coverage in order to improve access to care for patients of low socioeconomic status. There was a significant barrier to accessing spine care for patients with Medicaid insurance. Access was greatest for those with private insurance followed by those with Medicare. This study demonstrates that there is a significant disparity in ability to access spine specialists despite having insurance coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…However, it is also well known that Medicaid patients have poor odds of accessing direct orthopaedic care. 17,23,26 Our results demonstrate that this comes at a significant cost to the healthcare system, as accessing care through the ED added $4587 to the total cost of care.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, it is also well known that Medicaid patients have poor odds of accessing direct orthopaedic care. 17,23,26 Our results demonstrate that this comes at a significant cost to the healthcare system, as accessing care through the ED added $4587 to the total cost of care.…”
Section: Discussionmentioning
confidence: 83%
“…In particular, patients who have Medicaid have been shown to have poor access to orthopaedic care. 17,23,26 Areas that have a higher density of Medicaid enrollees could thus benefit from expanded provider coverage. This could include primary care sports medicine physicians or advanced practice providers at urgent care orthopaedic clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Access to care in orthopaedics, especially after the PPACA, has been a popular topic of discussion in orthopaedic research. 13,18,29 This study sought to examine access to orthopaedic care for urgent sports medicine patients based on the insurance they possessed. In the literature, there was a similar study published in 2017 looking at access to care based on insurance.…”
Section: Discussionmentioning
confidence: 99%
“…35 In a similar study conducted with regard to access to orthopaedic spine surgeons, patients with Medicare were unable to book appointments. 29 Studies have shown that patients with low socioeconomic status have a negative disparity in their health. 7,27 The purpose of Medicaid is to provide low-income patients with insurance, 33 and while expanding Medicaid may provide some patients with insurance that they would otherwise lack, it fails to grant them equal access to care when compared to patients with other insurance types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation